Factor Relating to Clean And Healthy Living Behavior (PHBS) In SDN 160 Kota Pekanbaru (HEALTH CARE: JURNAL KESEHATAN, 2025)
PHBS is a set of behaviors that are practiced on the basis of awareness as a result of learning which enables a person or family to help themselves in the field of health and play an active role in realizing the health of their community. Hygiene problems that many elementary school students still experience are dental problems as much as 86%, no 53% can cut their nails, 42% cannot brush their teeth and 8% cannot wash their hands before eating. Meanwhile, the diseases that many elementary school students suffer from are worms at 60-80%, and dental caries at 74.4%. Therefore, to overcome this problem there needs to be a comprehensive effort from various sectors. Children who are unfit, unhealthy, or don't care about PHBS have obstacles in the process of learning and teaching activities, such as having difficulty focusing or concentrating in receiving material, feeling sleepy, often feeling unable to complete assignments at home due to illness. . Initial survey results at SDN 160 Pekanbaru City, there are still many students who have not implemented clean and healthy living behavior (PHBS) in the school environment. This research uses a quantitative descriptive research method with a cross-sectional design. This research was conducted in May-June 2023. The population in this research was all 140 students of SDN 160 Pekanbaru City. The data analysis used is univariate analysis and bivariate analysis. The sampling technique uses total sampling technique.